The Conduction Pathways of the Brain and Spinal Cord: Structure, Function, and Clinical Significance - Muxlisa Qaxxorova (Scientific Trends, 2024)
This article discusses the anatomical structure and physiological functions of the brain and spinal cord conduction pathways. These pathways play a vital role in transmitting neuronal impulses to various parts of the central nervous system. This article provides detailed information about the structure, disruptions, and clinical significance of these pathways.